Implementasi Pembelajaran Tematik untuk Meningkatkan Literasi di Tingkat Sekolah Menengah Pertama: Studi Korelasional pada Pembelajaran Bahasa Indonesia - Muhammad Faisol; Quthny, Abu Yazid Adnan; Susetya, Hemas Haryas Harja (Hasta Wiyata, 2025)
This study aims to identify the relationship between thematic learning and literacy strategies in Indonesian language learning at SMP Raudlatul Muta'allimin Dawuhan in the 2024/2025 academic year. Data were collected through tests and questionnaires. This study uses a quantitative method with Pearson correlation analysis, and is supported by data from questionnaires distributed to students. The results of the study showed a Pearson correlation value of r = -0.08, which is included in the category of a very weak and negative relationship, and only around 23.75% of students stated that they strongly agreed that thematic learning helps improve their literacy. These findings indicate that although thematic learning has been proven effective at the elementary school level, this approach does not necessarily have a positive effect at the junior high school level without appropriate adjustments. Therefore, this study recommends that teachers and schools develop a thematic learning model that is more relevant to the needs and characteristics of junior high school students and integrate literacy strategies in a more targeted manner.